Mário de Andrade and the First of May, 1935 - Costa, Iná Camargo (1995)
Mário de Andrade wrote his short story, Primeiro de Maio, between 1934 and 1942. Is was posthumously published in his collection of stories Contos Novos. The following reading dates its action and tries to highlight aspects of the history of the working class struggle. Those aspects are not only related to the day but also stem from this short story formal devices.